Tumor Necrosis Factor Superfamily 14 drives the depletion of tissue-resident alveolar macrophages upon influenza A virus infection enabling the establishment of secondary pneumococcal pneumonia - Malainou, Christina; Justus Liebig University Giessen (My University, 2023)
Tissue-resident alveolar macrophage (TR-AM) depletion is a key event upon influenza A virus (IAV)-induced pneumonia and one of the most important contributors to the establishment of post-viral pneumococcal pneumonia, a common complication of severe IAV infection. However, the mechanisms behind TR-AM death remain largely unknown. In the current study, the time frame, mechanisms, and related signaling pathways behind TR-AM loss after IAV infection were analyzed, proposing a novel mechanism for the preservation of the TR-AM pool through targeting of the tumor necrosis factor superfamily member 14 ligand-receptor axis. This offer a novel therapeutic approach both for IAV pneumonia and for secondary post-influenza pneumococcal infection.
Keywords: Influenza; ddc:610